AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN READING ACADEMIC TEXT (A Qualitative Study at One of Universities in Garut) - Tri Suci Adilla; Tanto Setia Muljanto (Institut Pendidikan Indonesia Garut, 2020)
The aims of this study were to investigate what kind of the difficulties in comprehending academic text and factors that caused the students’ difficulties in comprehending academic text that have been faced by English Department students university in Garut. The participants were five semester students. The data were collected by demographic questionnaire and interviews with the English department students. The result showed that the English students faced four difficulties in comprehending their text in five semesters. The difficulties included four major themes, vocabulary, working memory, absence of extensive reading and type of text. Then, there were seven factors students’ difficulties in comprehending academic text that affected English students. They were, vocabulary level, comprehension ability, physical stated, stated of mind, interest in material and background knowledge. The conclusions of this study are the students faced difficulties in comprehending their text in their course and also there were seven factors which make them difficult to comprehend their textbooks.